Digital Marketing untuk Penguatan Penjualan UMKM - Putra Armawan; Glorysha Simbolon; Kholillah Azahra Barus; Raka Ayub Pratama; Dionisius Sihombing; Fadli Agus Triansyah (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
The development of digital technology has brought significant changes to marketing strategies, including in the Micro, Small, and Medium Enterprises (MSME) sector. This study aims to design a digital marketing strategy that can increase sales at Lontong Bang Haji MSMEs in Medan City. The research method uses a case study approach with data collection through interviews, observation, and documentation. Data analysis was conducted using descriptive qualitative methods to describe the marketing practices implemented and the effectiveness of the digital media used. The results of the study show that the use of social media, particularly Instagram and WhatsApp Business, is the most effective strategy for expanding market reach, increasing interaction with consumers, and building brand awareness. The main challenges faced include time constraints, technical knowledge limitations, and digital promotion budgets. However, the integration of offline and online promotions has proven to enhance the competitiveness of SMEs. Thus, a simple yet consistent digital marketing strategy can serve as a practical solution for SMEs to expand their market and drive sales growth.